Ascoma genotyping and mating type analyses of mycorrhizas and soil mycelia of Tuber borchii in a truffle orchard established by mycelial inoculated plants. (20th August 2019) - Leonardi, Pamela; Murat, Claude; Puliga, Federico; Iotti, Mirco; Zambonelli, Alessandra
Summary: Tuber borchii (the Bianchetto truffle) is a heterothallic Ascomycete living in symbiotic association with trees and shrubs. Maternal and paternal genotype dynamics have already been studied for the black truffles Tuber melanosporum and Tuber aestivum but not yet for T. borchii . In this study, we analysed maternal and paternal genotypes in the first truffle orchard realized with plants inoculated with five different T. borchii mycelia. Our aims were to test the persistence of the inoculated mycelia, if maternal and/or paternal genotypes correspond to inoculated mycelia and to assess the hermaphroditism of T. borchii . The mating type of each isolate as well as those of mycorrhizas, ascomata and extraradical soil mycelia was determined. Moreover, simple sequence repeat (SSR) profiles of maternal and paternal genotypes were assessed in 18 fruiting bodies to investigate the sexual behaviour of this truffle. The maternal genotypes of the fruiting bodies corresponded to those of the inoculated mycelia with only two exceptions. This confirmed that the inoculated mycelia persisted 9 years after plantation. As regards paternal partner, only two had the same genotype as those of the inoculated mycelia, suggesting hermaphroditism. Most of the new paternal genotypes originated from a recombination of those of inoculated mycelia.